PEMANFAATAN AREAL BERMAIN UNTUK MENINGKATKAN KEMAMPUAN MOTORIK DAN SENSORIK ANAK TK PERTIWI DUSUN SEMAYA, KARANGLEWAS - Yudi Suryadi; Diana Puspitasari; Heri Widodo (Jurnal Abdi Insani, 2022)
TK Pertiwi is the only kindergarten in Semaya hamlet which is located under the slopes of Mount Slamet, which is about 18 km from downtown Purwokerto. Geographically, the hamlet is bordered by a protected forest area so Semaya seems to be separated from urban civilization. This also has an impact on the lack of learning support facilities. The lack of infrastructure to support creativity and children's motor and sensory abilities encourages the service team to use land in the kindergarten area. The purpose of this service is to provide a vast space for children to move and explore creative abilities to support children's motor and sensory development. The method used consists of 3 stages, namely 1) pre-preparation includes identification of the target audience, collection, and analysis of needs. 2) Preparation includes identification of procurement of goods, purchases, and determination of time and accommodation. 3) Implementation of activities in accordance with the activity plan that has been formulated.The activities carried out in the service are the installation of outdoor game equipment on the vacant land of the kindergarten area in the form of trampolines and slides. The second activity is land use for gardening areas where 1 child gets vegetable seeds and gardening equipment consisting of pots, fertilizer soil media, mini shovels, and mini plant waterers. The last activity is a musical activity where children learn to recognize the notation in the piano by blowing and pushing the keys. Besides aiming to help children's motor and sensory development from an early age, it also instills a love and sensitivity to the environment in one of its activities. The implementation of this activity provides great benefits for kindergarten and children. For children, the facilities provided can help motor and sensory development through the activities carried out.